Analysis of the anomie behavior and external motivation of college students in sports: A cross-sectional study among gender - Liu, Liping; Chen, Shanping; Yang, Xueyan (Frontiers in Psychology, 2022)
Objective In the context of Healthy China, the effect of external motivation on sports anomie behavior from the perspective of gender among Chinese college students was investigated. Participants In total, 2,340 college students were involved in this study. Methods The self-made scales were used, which were about anomie behavior and external motivation in sports. The independent sample T-test was used to compare the sports anomie behavior between male and female students. Then, multiple linear regression analysis was adopted to examine the effects of external motivation on sports anomie behavior. Results Girls’ sports anomie behavior was lower than boys. There were significant gender differences in honor motivation, obedience motivation, and economic motivation; girls’ motivations were lower than boys. The academic motivation was negatively correlated with the sports anomie behavior of college students of both genders. The economic motivation was positively correlated with their sports anomie behavior. The honor motivation was negatively correlated with the sports anomie behavior of female college students. Conclusion Female college students’ sports anomie behavior and external motivation are lower than that of male college students. External motivation had a significant influence on college students’ sports anomie behavior.